Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1021/jp4072795
|View full text |Cite
|
Sign up to set email alerts
|

Twin Induced Sensitivity Enhancement of HMX versus Shock: A Molecular Reactive Force Field Simulation

Abstract: We report the early events of a twinned HMX crystal, as well as a perfect one for a comparison purpose, shocked with various velocities in the range of 6–10 km/s for 50 ps by molecular dynamic simulations using the ReaxFF reactive force field and the multiscale shock technique. The simulations show that the twin enhances the shock sensitivity remarkably, in agreement with our recent experimental observation. That is, it exhibits a lower shock initiation stress, higher decomposition velocities, more temperature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
60
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(68 citation statements)
references
References 29 publications
(55 reference statements)
7
60
0
Order By: Relevance
“…Instead of simulating a shock wave within a large computational cell with many atoms, the computational cell of the MSST method follows a Lagrangian The Journal of Physical Chemistry B Article point through the shock wave, enabling the simulation of the shock wave with really fewer atoms and significantly lower computational cost. This technique had been successfully tested on simulating of NM, 35 TATB, 36 and HMX 20,23,29,37 under the shock wave loading and shown to be an accurate prediction of physical and chemical behaviors.…”
Section: Computational Detailsmentioning
confidence: 99%
“…Instead of simulating a shock wave within a large computational cell with many atoms, the computational cell of the MSST method follows a Lagrangian The Journal of Physical Chemistry B Article point through the shock wave, enabling the simulation of the shock wave with really fewer atoms and significantly lower computational cost. This technique had been successfully tested on simulating of NM, 35 TATB, 36 and HMX 20,23,29,37 under the shock wave loading and shown to be an accurate prediction of physical and chemical behaviors.…”
Section: Computational Detailsmentioning
confidence: 99%
“…The computational cell could be simulated with fewer atoms and lower computational cost by following a Lagrangian point through the shock wave. [14] Currently, the molecular dynamics method based on MSST have been applied in HMX [15] , TATB [16] , and graphite [17] and so on. In this work we report DFTB-MD simulation of the shock Hugoniot of water, using MSST module in LAMMPS [18] in conjunction with DFTB+ [19] 0 and δ=90 0 .…”
Section: Computational Detailsmentioning
confidence: 99%
“…Wen et al [43] used ReaxFF-MD to demonstrate that twinned HMX crystals are much more shock sensitive than perfect HMX crystals. Long and Chen [16] studied the reaction kinetics of HMX by using ReaxFF-MD and observed that the detonation velocity and pressure agreed very well with experimental results.…”
Section: Introductionmentioning
confidence: 99%